1991
DOI: 10.1073/pnas.88.15.6481
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin mutations in autosomal dominant retinitis pigmentosa.

Abstract: DNA samples from 161 unrelated patients with autosomal dominant retinitis pigmentosa were screened for point mutations in the rhodopsin gene by using the polymerase chain reaction and denaturing gradient gel electrophoresis. Thirty-nine patients were found to carry 1 of 13 different point mutations at 12 amino acid positions. The presence or absence of the mutations correlated with the presence or absence of retinitis pigmentosa in 174 out of 179 individuals tested in 17 families. The mutations were absent fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
236
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(244 citation statements)
references
References 17 publications
8
236
0
Order By: Relevance
“…Pro-347-Arg (CCG--,CGG) mutation was observed in a Swiss family (Gal et al, 1991). As to codon 17 in exon 1, the Thr-17-Met (ACG~ATG) mutation detected in our study has been observed in the United States Sung et al, 1991a;Richards et al, 1991;Fishman et al, 1992). The codon 58 mutation reported in the United States was absent among 24 families in the present study.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Pro-347-Arg (CCG--,CGG) mutation was observed in a Swiss family (Gal et al, 1991). As to codon 17 in exon 1, the Thr-17-Met (ACG~ATG) mutation detected in our study has been observed in the United States Sung et al, 1991a;Richards et al, 1991;Fishman et al, 1992). The codon 58 mutation reported in the United States was absent among 24 families in the present study.…”
Section: Discussionsupporting
confidence: 48%
“…Now, more than 26 different kinds of single-base mutations and a few cases of deletion of codon (s) within the coding region of rhodopsin gene have been identified in ADRP patients (Inglehearn et al, 1991;Keens et al, 1991 ;Sung et al, 1991a;Dryja et al, 1991, etc.). Moreover, it has been identified that at least two distinct biochemical defects have been associated with different rhodopsin mutants in ADRP (Sung et al, 1991b).…”
Section: Discussionmentioning
confidence: 99%
“…Multiplex ligation-dependent probe amplification was normal, excluding a copy-number variant on the second allele as an explanation for the phenotype (Supplementary Figure S2 online). An F45L substitution has been reported to be pathogenic in ADRP patients, [29][30][31] however, the pathogenic mechanism could not be identified. 10 Bioinformatic analyses were inconclusive; the residue at site 45 is invariant across vertebrates (Supplementary Figure S1 online) and is found on the outer surface of the first TMD (Figure 2a and Supplementary Figure S3 online), but the Grantham score predicts that the effect of the F45L substitution should be minimal ( Table 2).…”
Section: Validation Of Functional Analysesmentioning
confidence: 99%
“…Mutations in rhodopsin gene Sung et al, 1991a;Inglehearn et al, 1992;Macke et al, 1993), peripherin/RDS gene (Farrar et al, 1991;Kajiwara et al, 1991) and other candidate genes have been found in patients with RP. In Japan, three families with Thr-17-Met , Glu-181-Lys (Saga et al, 1994), or Pro-347-Leu mutation in the rhodopsin gene, and two families with Cys-214-Ser (Saga et al, 1993) or Asn-244-Lys mutation (Kikawa et al, 1994) in the peripherin/RDS gene have been reported as autosomal dominant RP (ADRP).…”
Section: Introductionmentioning
confidence: 99%